Risk Factors Related to Recurrence Rates of Acute Coronary Syndrome in Pakraman and Non-Pakraman Villages in Bali Province - Ni Luh Sri Wahyuni; Tina Handayani Nasution; Edy Widjajanto (Research Journal of Life Science, 2020)
The prevalence of Acute Coronary Syndrome (ACS) is increasing in both developed and developing countries. Uncontrolled risk factors such as smoking, hypertension, and fewer activities are the main causes of ACS recurrence within 30 days after the acute presentation. This study aims to analyze risk factors related to the recurrence rate of ACS patients in Pakraman and non-Pakraman villages in Buleleng Regency, Bali Province. Observational analytics with Cross-Sectional Study are used in this study involving 130 patients within 1 month. Data is collected through two (2) stages using a questionnaire. The bivariate analysis shows that both smoking groups (p = 0.003 and p = 0.008) and hypertension groups (p = 0.02 and p = 0.01) are associated with ACS recurrence, while physical activity groups are not related (p = 0.455 and p = 0.565). Logistic regression results show that smoking (5.633) is highly associated with ACS recurrence in Pakraman villages, while hypertension (4.784) is highly associated with ACS recurrence in non-Pakraman villages. ACS handling is important in the acute period and in the long-term to prevent the risk of recurrence.